Analisis Efektivitas Pengelolaan Anggaran Pendapatan Dan Belanja Desa (APBDes) Desa Purwosari, Kabupaten Magetan Tahun 2019-2022 - Panca Safira Amelia,; Irvan Bari Alghani,; Nuwun Priyono, (Jurnal Mutiara Ilmu Akuntansi, 2023)
This study aims to analyze the realization of the management of the Village Revenue and Expenditure Budget. Village Revenue and Expenditure Budget is an important financial instrument in managing village finances to finance various development activities and public services at the village level. In this study, we use methods to study the implementation of Village Revenue and Expenditure Budget management in different contexts. The data used includes the budget that has been allocated, the realization of expenses, and related financial reports. Apart from that, we also involved interviews with related parties such as village financial managers, village heads, and community members. The results of this study indicate that there are still some problems in managing the Village Revenue and Expenditure Budget. Some of them are a lack of understanding of the budgeting process, weaknesses in monitoring and evaluating budget use, and low community participation in decision-making processes related to Village Revenue and Expenditure Budget. In addition, there were also indications of misuse of funds and corrupt practices that needed to be followed up by the competent authorities. This study provides recommendations for improving the management of village budgets, including strengthening the capacity of village financial managers, increasing transparency and accountability in village financial reporting, and increasing participation the community in making decisions related to the management of the APBDes. It is hoped that the results of this research can provide valuable input for the village government and related stakeholders to increase the effectiveness and efficiency of Village Revenue and Expenditure Budget management in order to realize sustainable development at the village level.